Sacrococcygeal Teratoma in a Teen - A Case Report - Rahman, Md K; Haq, SMM; Sarker, AK; Shahid, SMA; Islam, MB (TAJ: Journal of Teachers Association, 2009)
Sacrococcygeal teratoma is a common congenital neoplasm. This tumor contains derivatives of more than one of the three embryonic germ cell layers e.g. ectoderm, mesoderm & endoderm and usually arises as a mass in the sacrococcygeal region. Here we are reporting a case of huge sacrococcygeal teratoma presenting as a lower abdominal and perineal mass in a thirteen-yearold schoolgirl, which is very rare. doi: 10.3329/taj.v16i2.3888 TAJ December 2003; Vol.16(2): 76-78